Role of Vitrectomy in the Treatment of Diabetic Retinopathy - D. V. Petrachkov; E. N. Korobov; D. D. Arzhukhanov (Oftalʹmologiâ)
Diabetic retinopathy (DR) is a socially significant disease with a steady tendency to increase, in which there is a high risk of disability due to persistent loss of vision. There are three main pathogenetically substantiated methods of DR treatment: laser coagulation of the retina; intravitreal injections of VEGF inhibitors, steroid drugs; vitreoretinal surgery. In the later stages of DR, vitrectomy is the main method of its complications treating, but there is no clear understanding of the timeliness of this operation. The analysis of the results of original research on this problem is carried out. It has been shown that with the advent of new instruments, modified vitrector, operating microscopes, viewing systems and vitreoretinal combines, vitrectomy led to a change in the paradigm of DR treatment. These advances have resulted in better surgical control and greater precision, while at the same time shorter surgical times and fewer surgical complications. There is a tendency to perform vitrectomy at earlier stages of DR, which has a pathogenetic rationale. This could be a leap forward in the treatment of DR as a preventive measure against the development of proliferative DR.